Antenatal care during the COVID-19 pandemic - Pitale, Devdatt Laxman (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: COVID-19 pandemic has affected the daily living globally. It has added to the stress of day to day life. COVID-19 is associated with severe disease in high-risk population groups with increased mortality risk. COVID-19 and it’s impact on pregnancy needs extensive research. Early research data does not suggest any increased risk in the pregnant population and Vertical transmission is yet to be confirmed. As of now no standard protocol is available for management of COVID-19 .Social distancing is the best possible mechanism available to protect patients and health care personnel from COVID-19. The aim of this study is to know the effectiveness of protocol based Antenatal care during COVID-19 pandemic. Methods: This study was conducted at the Antenatal clinic. A total of 40 antenatal cases who satisfied inclusion and exclusion criteria were selected for the above study. They were assessed at the antenatal clinic following a modified protocol. Results: Majority of the pregnant women in the study group were primigravidas and belonged to the age group of 21-25 years. They were called for Antenatal check-ups as per the protocol specifically modified taking into consideration the COVID-19 pandemic. 80% of the deliveries in present study were normal delivery and only in obstetric emergencies LSCS was performed. Conclusions: Antenatal care in COVID-19 pandemic is challenging yet essential. Following a protocol based approach is the key to management of Antenatal care amidst the pandemic. It is cost-effective and has an easy learning curve.